Pengaruh Earnings Management, Kepemilikan Institusional, Dan Corporate Governance Perception Index (Cgpi) Terhadap Biaya Utang - Nur Afni Yunita; Rany Gesta Putri Rais; Muhammad Yusra; Afisha Tirta Surya Lestari (Faculty of Economics and Business, Universitas Malikussaleh, 2023)
The objective of this research is to examine of earnings management, Institutional Ownership and Corporate Governance Perception index on the Cost of Debt. Data collected by purposive sampling method since 2018-2020 and gotten 15 companies that received GCG Award at IICG and SWA Magazine. Data analyzed by using panel regression. The result of research show that earning management has a negative effect on the cost of debt. But institutional ownership and Corporate Governance Perception Index (CGPI) has no effect on the cost of debt.